Colonization of two mycorrhizal fungi of Artemisia roots at reproductive stage respond complementarily to large-scale environmental gradients - Wenqiang Tang; Shuxin Shi; Ruixin Zhang; Ruiru Gao; Xuejun Yang (Rhizosphere, 2026)

“One stone two birds” strategy for sustainable water purification: Bifunctional photothermic-catalytic manganese oxide/carbon composites enabling solar evaporation, seawater desalination and periodate activation - Jing Jiang; Xiaojing Lai; Yu Fang; Ruiru Yang; Xinyu Zheng; Song Tian; Fenfen Yang; Aike Liu; Lunhong Ai (Desalination, 2025)

Porous rGO-MBene monolith: A highly efficient solar evaporator for salt-resistant desalination and multitasking water purification - Mingming Chang; Ruiru Yang; Xiaojing Lai; Xinzhi Wang; Jing Jiang (Desalination, 2024)

Photothermic-catalytic bifunctionality of boron-doped molybdenum disulfide nanosheets enabling simultaneous solar evaporation and antibiotic destruction - Mingming Chang; Ruiru Yang; Xiaojing Lai; Xinzhi Wang; Aike Liu; Jing Jiang (Chemical Engineering Journal, 2024)

Two-dimensional layered MBene membrane towards sustainable freshwater production from solar interfacial evaporation - Mingming Chang; Lunhong Ai; Ruiru Yang; Xinzhi Wang; Ying Xu; Jing Jiang (Chemical Engineering Journal, 2024)

Biomass-derived three-dimensional robust solar evaporator for efficient steam generation, water purification and salt-resistant desalination - Jing Jiang; Ruiru Yang; Fanyi Zeng; Sheng Tu (Chemical Engineering Journal, 2024)

Hierarchical Co3S4 nanostructure coupling with macroporous nickel foam: A robust interfacial solar evaporator for efficient desalination and sustainable freshwater production - Jing Jiang; Ruiru Yang; Xian Lu; Lunhong Ai (Desalination, 2024)

Integrated solar evaporator based on photothermal Cu-CuOx/NC with heat-insulated polyurethane foam enabling highly efficient salt-tolerant desalination and water purification - Jing Jiang; Ruiru Yang; Zerong Tao; Sheng Tu (Desalination, 2024)

Geographical variation of Artemisia leaf morphology along a large environmental gradient in China - Xinyu Hou; Ruiru Gao; Liping Huo; Xiaoxia Yu; Xuejun Yang (Plant Ecology, 2023)

Fine mapping of KLW1 that conditions kernel weight mainly through regulating kernel length in wheat (Triticum aestivum L.) - Yang Yang; Zhongxin Kong; Quan Xie; Haiyan Jia; Wenshuo Huang; Liwei Zhang; Ruiru Cheng; Zibo Yang; Xiaolei Qi; Guangde Lv; Yong Zhang; Yixuan Wen; et al. (Theoretical and Applied Genetics, 2023)

Coordination of economics spectra in leaf, stem and root within the genus Artemisia along a large environmental gradient in China - Rong Liu; Xuejun Yang; Ruiru Gao; Zhenying Huang; Johannes H. C. Cornelissen (Global Ecology and Biogeography, 2023)
Aim The plant economics spectrum provides a fundamental framework for understanding functional trait variation along environmental gradients. However, it is unclear whether there is a general whole‐plant economics spectrum across organs at the finer taxonomic scale (e.g. within genera), and if there is, which factors affect the trait coordination of the different organs. Here, we examined whether resource economics spectra of different organs (i.e. leaf, stem and root) can be integrated at the whole‐plant level within a single genus, and how environment, intraspecific variation and taxonomic scale shape the whole‐plant spectrum. Location China. Time period 2018. Major taxa studied Artemisia . Methods We sampled 1,022 individuals of 62 Artemisia species in central and eastern China to test trait coordination patterns from organ to whole‐plant level. From the resource economics spectrum perspective, 15 traits were chosen to represent the trade‐off between structural and nutrient investments, including organs’ C, N, P and dry matter content, specific leaf area, specific stem length and specific root length. Results Pairwise trait correlations and the trade‐off patterns along the resource economic axis were consistent at both organ and whole‐plant levels. Environmental gradients did not strongly affect the correlations among leaf, stem and root economics spectra, that is, the intraspecific variation weakened but did not mask this coordination. Taxonomic scale did not affect the degree of trait coordination as the genus‐wide whole‐plant economics spectrum also emerged within each of the three subgenera. Main conclusions Our results support the hypothesis that the coordination of economics spectra across organs forms a whole‐plant economics spectrum representing a ‘fast–slow’ resource management strategy, which is robust to recent evolution (genotypic variation, even for species within a single genus) and present‐day environmental variation. Further studies should elucidate in which circumstances or phylogenetic branches the coordinated pattern found for Artemisia is representative of other widely distributed genera.

Net plant interactions are highly variable and weakly dependent on climate at the global scale - Xuejun Yang; Lorena Gómez‐Aparicio; Christopher J. Lortie; Miguel Verdú; Lohengrin A. Cavieres; Zhenying Huang; Ruiru Gao; Rong Liu; Yonglan Zhao; Johannes H. C. Cornelissen (Ecology Letters, 2022)
Although plant–plant interactions (i.e. competition and facilitation) have long been recognised as key drivers of plant community composition and dynamics, their global patterns and relationships with climate have remained unclear. Here, we assembled a global database of 10,502 pairs of empirical data from the literature to address the patterns of and climatic effects on the net outcome of plant interactions in natural communities. We found that plant interactions varied among plant performance indicators, interaction types and biomes, yet competition occurred more frequently than facilitation in plant communities worldwide. Unexpectedly, plant interactions showed weak latitudinal pattern and were weakly related to climate. Our study provides a global comprehensive overview of plant interactions, highlighting competition as a fundamental mechanism structuring plant communities worldwide. We suggest that further investigations should focus more on local factors (e.g. microclimate, soil and disturbance) than on macroclimate to identify key environmental determinants of interactions in plant communities.

Fine mapping KT1 on wheat chromosome 5A that conditions kernel dimensions and grain weight - Zhongxin Kong; Ruiru Cheng; Haisheng Yan; Haiyun Yuan; Yong Zhang; Guoqiang Li; Haiyan Jia; Shulin Xue; Wenling Zhai; Yang Yuan; Zhengqiang Ma (Theoretical and Applied Genetics, 2022)

Seed dormancy and germination of a critically endangered plant, Elaeagnus mollis, on the Loess Plateau of China - Ruiru Gao; Jing Hou; Ruihua Zhao; Xuejun Yang; Xinyu Hou; Liping Huo; Siti N. Hidayati; Jeffrey L. Walck (European Journal of Forest Research, 2021)

Effects of rainfall pattern on the growth and fecundity of a dominant dune annual in a semi-arid ecosystem - Ruiru Gao; Xuejun Yang; Guofang Liu; Zhenying Huang; Jeffrey L. Walck (Plant and Soil, 2015)

Hydrated mucilage reduces post-dispersal seed removal of a sand desert shrub by ants in a semiarid ecosystem - Xuejun Yang; Carol C. Baskin; Jerry M. Baskin; Ruiru Gao; Fan Yang; Lingling Wei; Leilei Li; Hongju He; Zhenying Huang (Oecologia, 2013)